Understanding the Accessibility Barriers Faced by Learners with Visual Impairments in Computer Programming - Zen, Eliana; Da Costa, Vinicius Kruger; Tavares, Tatiana Aires (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2023: Anais do XXII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2023)
Assistive Technology (AT) has facilitated the integration and inclusion of people with disabilities in society. Regarding the visually impaired, the use of AT can be crucial in ensuring access to Information and Communication Technologies. However, in technical and higher-level courses related to computing, the use of AT may not be sufficient to ensure that these students comprehend the concepts addressed in the subjects and have access to all the resources provided by the tools necessary for their professional training. This is because screen readers, the main accessibility resource used by the visually impaired to interact with digital systems, generally perform a linear reading of the content available in the graphical interface, which can demand more time and effort from users. Additionally, this approach may limit access to information. This is particularly relevant in the case of Integrated Development Environment (IDEs), which have complex visual interfaces that may not be accessible to screen readers if accessibility requirements are not correctly implemented. Therefore, this study seeks to identify the barriers to interaction with IDEs faced by students in Computer Programming classes. The research involved surveying 12 professors of disciplines related to the area of Computer Programming who taught students with visual impairment. Additionally, interviews were conducted with 6 students and graduates with visual impairments from Technical and Higher Education courses in the area of Computing. The data were analyzed using Content Analysis. The results confirmed those already identified in the literature and also revealed new barriers.